Psicoesferas e consciência política: uma leitura psicopolítica das Fake News - Silva Junior, Ezio Alves da (2021)
The present study seeks to understand how social media (psychospheres) operate in the production of political consciences and to reflect on their impact on liberal democracies. Specifically, we seek to understand the relationship between the understanding of the true and the false, linked to the collective identity of the research participants. As a methodology we use the quantitative approach and psychosocial perspective. We work with two main categories within the political conscience model proposed by Salvador (2001), political identity, political efficacy and we also consider emotional feelings. We structured a questionnaire with 36 questions, ten of which presented images / news calls and the research participants needed to try to identify whether the images were true or false. The sample has 365 participating individuals who answered the questionnaire between October 10, 2018 and December 12, 2018, a period that partially crosses the electoral period. The questionnaire was applied to several Facebook groups and WhatsApp groups. The analysis of the data took place through the discrimination of the political identity of the participants and their respective evaluation / correlation with the fake news, we also deal with the sociodemographic variables; gives political effectiveness; corporate beliefs and values. Our first hypothesis (H1) is based on the premise of fake news as an actor of tensioning affections and political identities. As a result, we found a significant correlation (p> 5%) between political identity and the images in the questionnaire, which are perceived as true or false depending on how the participant identifies himself politically. We found a significant correlation (p> 5%) between political effectiveness and income. It was also possible to observe descriptively how users feel anger / hatred when seeing fakenews. As a conclusion, we consider that fake news is instrumentalized to permanently tense political identities, affections and even democracies insofar as psychospheres produce parallel realities